Optimal Taxation of Education with an Initial Endowment of Human Capital - Christoph Braun (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Bovenberg and Jacobs (2005) and Richter (2009) derive the education effi ciency theorem: In a second-best optimum, the education decision is undistorted if the function expressing the stock of human capital features a constant elasticity with respect to education. I drop this assumption. The household inherits an initial stock of human capital, implying that the aforementioned elasticity is increasing. In a two-period Ramsey model of optimal taxation, I show that the education effi ciency theorem does not hold. In a second-best optimum, the discounted marginal social return to education is smaller than the marginal social cost. The household overinvests in human capital relative to the first best. The government eff ectively subsidizes the return to education. – – Bovenberg und Jacobs (2005) und Richter (2009) leiten das Bildunseffizienztheorem her: In einem zweitbesten Optimum ist die Bildungsentscheidung unverzerrt, wenn die Funktion, die den Bestand an Humankapital beschreibt, über eine konstante Elastizität in Bezug auf Bildung verfügt. Diese Annahme lasse ich fallen. Der Haushalt erbt einen Anfangsbestand an Humankapital, was dazu führt, dass die vorgenannte Elastizität steigend ist. In einem Ramsey-Modell der optimalen Besteuerung mit zwei Perioden zeige ich, dass das Bildunseffizienztheorem nicht gilt. In einem zweitbesten Optimum gilt, dass der abdiskontierte soziale Grenzertrag kleiner ist als die sozialen Grenzkosten. Der Haushalt überinvestiert in Humankapital relativ zur erstbesten Lösung. Die Regierung subventioniert effektiv den Ertrag der Bildung.
Keywords: H21; I28; J24; 330; optimal taxation; human capital